2019
DOI: 10.1136/jclinpath-2019-206055
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiolar pattern and albumin in situ hybridisation enable a diagnosis of intrahepatic cholangiocarcinoma

Abstract: AimsThe histological distinction of intrahepatic cholangiocarcinoma (ICC) from metastatic adenocarcinoma remains a challenge. The primary goal was to evaluate the diagnostic value of morphology and albumin expression in the diagnosis of ICC.MethodsWe evaluated morphological patterns in 120 ICCs and 677 non-hepatic adenocarcinomas and performed in situ hybridisation (ISH) stain for albumin in the former coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Cholangiocarcinoma cell arising from cell proliferation after bile duct injury could be a form of undifferenciated cholangiocyte producing albumin. There are several reports on aberrant expression of albumin; it could be used to distinguish bile duct neoplasm from other metastatic adenocarcinoma [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Cholangiocarcinoma cell arising from cell proliferation after bile duct injury could be a form of undifferenciated cholangiocyte producing albumin. There are several reports on aberrant expression of albumin; it could be used to distinguish bile duct neoplasm from other metastatic adenocarcinoma [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…To establish the diagnosis of iCCA and distinguish it from other tumors, it is recommended that specific imaging observations are considered and analyzed [ 46 , 52 ]. HCC may be distinguished from iCCA based on radiological features on a contrast-enhanced imaging study; while HCC lesions show hyperenhancement in the arterial phase and contrast washout in the venous phase, iCCA shows progressive contrast uptake throughout both arterial and venous phases without a washout pattern [ 46 , 47 , 48 ].…”
Section: Identifying Potential Challenges and Solutions For Optimal Treatment Of Patients With Iccamentioning
confidence: 99%
“…Importantly, albumin in situ hybridization assays may aid pathologists in the diagnosis of iCCA and should be considered in the workup when iCCA is suspected. Research has shown that non-hepatic primary cancers are largely negative for albumin and that positive albumin in cancer cells has high sensitivity for iCCA [ 52 , 53 , 54 ]. While the assays can differentiate iCCA from liver metastases, it should be noted that it may not be useful in differentiating iCCA from HCC or pancreatic acinar cell carcinoma lesions; therefore, HCC and pancreatic acinar-specific markers should be used to rule out these tumors.…”
Section: Identifying Potential Challenges and Solutions For Optimal Treatment Of Patients With Iccamentioning
confidence: 99%
See 2 more Smart Citations